Emprego de dispositivo portátil no ensino de química: determinação de cloro residual livre em água potável - Rosar, Leandro (2020)
This work had as its theme the execution of a research / practice activity, with the students of the second year “A” of the 2019 academic year of the Colégio Estadual Tiradentes Elementary and High School, municipality of Umuarama state of Paraná, this activity, which aims to control the quality of drinking water, which directly impact the health conditions of the population. For this, the students were divided into 5 (five) groups, of six members each, the formation of the group (s) was at the discretion of the students. Then, a series of colorimetric analyzes was performed in the room to determine the concentration of residual free chlorine in drinking water, based on the reaction with DPD (dialkyl - 1,4 - phenylenediamine or N, N-diethyl-p-phenylene- diamina), according to the adaptation of official methodologies, with the aid of a smartphone application called Photometrix UVC®, in a Controlled Light Environment - ALC, and based on previously produced standards. Based on the comparison of the values obtained by the Photometrix UVC® application in a Controlled Light Environment with the reference device, the Hanna Instruments Chlorimeter - HI701 Free Chlorine®, it was found that the practical activity was effective to identify the Free Residual Chlorine of the samples analyzed, and the activity proved to be totally feasible to be carried out in the classroom and with reagent savings, due to the adaptation in the analysis method. It is worth mentioning that all the samples analyzed, brought by the students, met the current legislation that establishes minimum concentrations of chlorine in drinking water for human consumption.